Stimulation of autologous progenitorial and committed cells in ischemically damaged myocardium - A. I. Lebedeva; S. A. Muslimov; E. M. Gareev; S. V. Popov; S. A. Afanasiev (Российский кардиологический журнал, 2018)
Summary. Local progenitor cells are present in all tissues, including the myocardium. Stimulation of these cells can significantly improve the efficiency of the regeneration process. Biodegradation products of Alloplant biomaterials (ABM) are an inhibitor of fibrosis and serve as an inducer of stem cells in various body tissues including smooth and skeletal muscles, as well as connective tissue.Aim. To determine the cell regenerative potential of progenitorial c-kit and committed GATA-4 cells in ischemic myocardium on the background of ABM application in chronic experiment.Materials and methods. 100 Wistar rats weighing 180-200g were used, that underwent  ligation of coronary artery. In the experimental group (n = 50), 600 μl of a physiological solution containing 12 mg of ABM was administered simultaneously with coronary occlusion. General histological studies (hematoxylin and eosin staining, and staining as per Mallory), immunohistochemical (c-kit, GATA-4) and morphometric studies (determination of the index of the scar's area, counting of stained cells) were carried out. The statistical processing of the results was carried out using the rank methods - single factor dispersion analysis as per Kruskalou-Wallace and the comparison of uncorrelated data by the Mann-Whitney method.Results. When using ABM during coronary occlusion, myocardium was characterized by a statistically significant (p <0.0001) prevalence of c-kit+ / GATA-4+ cells numbers throughout the follow-up period (3-45 days). These cells were localized mainly in the granulation tissue of the peri-cicatricial area, bordering on the preserved cardiac muscle tissue. In the peri-cicatricial area, cardiac cells had a different degree of maturity - from poorly differentiated forms (without clear ultrastructural signs of cardiomyogenic orientation) to young cardiomyocytes. In the presence of ABM, coronary occlusion was characterized by statistically significantly smaller values of the index of the scar's area (p <0,05 ÷ <0,0001).Conclusion. ABM degradation products are chemoattractants for c-kit cells and promote their differentiation into cardiomyogenic GATA-4 cells, which contributes to more successful myocardium repair.